The capital barrier to innovation in the small and medium-sized enterprises - Lucyna Lewandowska (Comparative Economic Research. Central and Eastern Europe, 2009)
The article discusses SMEs' situation with reference to the process of creating an innovative economy. The presented discussion covers both non-material and financial barriers impeding the development of innovations. The examined range of new solutions designed to finance innovation includes types of capital support such as leasing, franchising, venture capital, Business Angels, NewConnect.
Keywords: 330